2008
DOI: 10.1073/pnas.0808757105
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of normal with mutant alleles in the genome of normal human cells unveils mutation-specific drug responses

Abstract: Mutations in oncogenes and tumor suppressor genes are responsible for tumorigenesis and represent favored therapeutic targets in oncology. We exploited homologous recombination to knock-in individual cancer mutations in the genome of nontransformed human cells. Sequential introduction of multiple mutations was also achieved, demonstrating the potential of this strategy to construct tumor progression models. Knock-in cells displayed allele-specific activation of signaling pathways and mutation-specific phenotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
124
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 95 publications
(138 citation statements)
references
References 34 publications
7
124
1
Order By: Relevance
“…Isogenic cell models able to effectively recapitulate single genetic aberrations have been employed extensively to establish binary drug-genotype associations (20,30,31). Nevertheless, limited efforts have been dedicated to dissect the role of combinations of mutations in determining drug response.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Isogenic cell models able to effectively recapitulate single genetic aberrations have been employed extensively to establish binary drug-genotype associations (20,30,31). Nevertheless, limited efforts have been dedicated to dissect the role of combinations of mutations in determining drug response.…”
Section: Discussionmentioning
confidence: 99%
“…All experimental procedures for BRAF V600E targeting vector construction, adeno-associated virus (AAV) production, cell infection, and screening for recombinants have been described previously (20,21).…”
Section: Construction Of Isogenic Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…SW48 cells are wt for KRAS, whereas SW48 KRAS G13D cells were created by knock-in of an activating mutation into one KRAS allele (Di Nicolantonio et al, 2008). We found that Snail2 knockdown using two small interfering RNA (siRNA) oligos differentially killed SW48 KRAS G13D cells, but had a minimal effect on SW48 wt cells (Figure 1d, Po0.01), even though Snail2 knockdown effects were stronger in SW48 wt cells (Supplementary Figure S1b).…”
Section: Snail2 In Ras Induced Emtmentioning
confidence: 96%